The "-6" is multiplied (distributed) across the parentheses: -6 * 4 and -6 * -3x, which is then -6 * 4 = -24 and -6 * -3x, which is then 18x.

Now you have -24 + 18x - 5x = x

Combine the x's. We need to subtract an "x" from both sides of the equation. This keeps the equation in balance.

-24 + 18x - 5x - x = x - x becomes -24 + 13x - x = 0 which becomes -24 + 12x = 0

Now, we solve for "x", subtracting "12x" from both sides of the equation. This keeps the equations in balance, again.

-24 +12x -12x = 0 - 12x become -24 = -12x.

Divide both sides by -12:

2 = x or

x = 2

Cross check

-6(4 - 3x) - 5x = x

-6(4 - 3(2)) - 5(2) = 2

-6(4 - 6) - 10 = 2

-6(-2) - 10 = 2

12 - 10 = 2

Got it...

Good luck

Bob